Puppets: a strategy to develop oral expression in French - Pachón Achury, Vitalia; Camargo Vargas, Diego Mauricio; Castro Herrera, Angela Rocío (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The objective of this article is to present the results of a research project carried out to explore how the use of puppets influences the development of oral expression in FFL in second grade students of the Gimnasio Ovidio Decroly school in Tunja. This study arises from a diagnostic study carried out previously, where the need to work on oral expression was discovered. Through a series of language workshops, it was possible to create an interaction between the puppet and the students. For data collection, three instruments were used: a field journal, a portfolio and a final video.The analysis of the data made possible to find the favorable effect of puppets on a better use of the lexicon, by using short sentences, making simple interactions answering and asking questions, allowing them to express themselves with more security and confidence. In addition, the students made their own puppets and learned how to play them. Finally,  the effects of puppetry on students as a tool to develop oral expression was discussed